2017
DOI: 10.1002/bies.201700104
|View full text |Cite
|
Sign up to set email alerts
|

Single‐cell Hi‐C bridges microscopy and genome‐wide sequencing approaches to study 3D chromatin organization

Abstract: Recent years have witnessed an explosion of the single-cell biochemical toolbox including chromosome conformation capture (3C)-based methods that provide novel insights into chromatin spatial organization in individual cells. The observations made with these techniques revealed that topologically associating domains emerge from cell population averages and do not exist as static structures in individual cells. Stochastic nature of the genome folding is likely to be biologically relevant and may reflect the abi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 61 publications
1
19
0
Order By: Relevance
“…Therefore, to uncover higher‐order chromatin organization in zygotes, we used a list of loop loci identified in CH12‐LX cells (Rao et al , ). For Hi‐C data on low numbers of cells (Ulianov et al , ), loops and TADs are most visible when averaged over multiple positions (Flyamer et al , ) and normalized relative to control regions that are selected from random shifts of loop loci (Appendix Fig S1A). Using our approach, we found that these data support the presence of loops and TADs in eight‐cell, two‐cell, and even one‐cell embryos (Fig B; Appendix Fig S1B) and are in agreement with previous findings that TADs and loops become stronger with progressing development (Du et al , ; Ke et al , ).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, to uncover higher‐order chromatin organization in zygotes, we used a list of loop loci identified in CH12‐LX cells (Rao et al , ). For Hi‐C data on low numbers of cells (Ulianov et al , ), loops and TADs are most visible when averaged over multiple positions (Flyamer et al , ) and normalized relative to control regions that are selected from random shifts of loop loci (Appendix Fig S1A). Using our approach, we found that these data support the presence of loops and TADs in eight‐cell, two‐cell, and even one‐cell embryos (Fig B; Appendix Fig S1B) and are in agreement with previous findings that TADs and loops become stronger with progressing development (Du et al , ; Ke et al , ).…”
Section: Resultsmentioning
confidence: 99%
“…2E ). Both DNA FISH 3,9,36–39 and single-cell Hi-C 40,41 studies show that genome organization is highly variable between cells and that even strong Hi-C loop anchors only contact in a small subset of cells, arguing that a simultaneous “loop rosette” occurs very rarely in a single cell.…”
Section: Tads Are Formed By Cohesin and Tad Boundaries Are Defined Bymentioning
confidence: 99%
“…A given high‐resolution TAD is related to an average structure of millions of chromatin domains (CDs) with the same DNA sequence. Single cell Hi‐C can provide data on TADs, whose 3D structure can be more directly compared with the 3D structure of individual TADs studied by advanced microscopy, (for review, see References 70 and 73). The greatly reduced number of contacts, which can be identified within the nucleus of an individual cell, however, goes hand in hand with a loss of Hi‐C resolution.…”
Section: Spatial Organization Of Regulatory Sequences Determined By Hi‐cmentioning
confidence: 99%